Double debiased machine learning nonparametric inference with continuous treatments - Kyle Colangelo; Ying-Ying Lee (Centre for Microdata Methods and Practice (cemmap), 2019)
We propose a nonparametric inference method for causal effects of continuous treatment variables, under unconfoundedness and in the presence of high-dimensional or nonparametric nuisance parameters. Our simple kernel-based double debiased machine learning (DML) estimators for the average dose-response function (or the average structural function) and the partial effects are asymptotically normal with nonparametric convergence rates. The nuisance estimators for the conditional expectation function and the conditional density can be nonparametric kernel or series estimators or ML methods. Using doubly robust influence function and cross-fitting, we give tractable primitive conditions under which the nuisance estimators do not affect the first-order large sample distribution of the DML estimators. We implement various ML methods in Monte Carlo simulations and an empirical application on a job training program evaluation to support the theoretical results and demonstrate the usefulness of our DML estimator in practice.
Keywords: C14; C21; C55; 330; Average structural function; cross-fitting; dose-response function; doubly robust; high dimension; nonseparable models; partial mean; post-selection inference